QUALITY RESEARCH MANAGEMENT IMPROVES DESIGN RESEARCH EFFECTIVENESS - Holm, Johann Erich Wolfgang; van der Merwe, G PR (The South African Journal of Industrial Engineering, 2019)
Design research projects are often more complex than initially perceived due to a requirement for novelty, the creativity inherent in the design process, and the limited experience of novice researchers. Also, expectations from institutions and external funding stakeholders must be met. Therefore, a framework was needed to support the research effort in the form of quality research management. The focus of this framework is primarily to align stakeholders. To this end, engineering management methods were consulted to define a quality research management framework that provides review baselines, requirements traceability, and a general process model. The framework is based on the well-known ‘house of quality’ principle that provides requirements traceability. A series of matrices was developed, with a research validation matrix resulting from the combination of traceability matrices. This matrix allows the allocation of research challenges to a need, concept solutions to research challenges, and specific research solutions to concept solutions. Also, information sources are allocated to challenges and solutions to verify their authenticity. It is thus possible to visualise clearly a summary of the research project. Additional benefits include improved communication, visualisastion of progress, traceability of requirements, and verification and validation, which illustrates the value of quality research management.